Radiological images of an advanced invasive carcinoma with mucinous aspects: A case report - Chiara Adriana Pistolese, MD, PhD; Francesca Di Giuliano, MD, PhD; Martina Cerocchi, MD; Maria Volpe, MD; Martina Cerasi Dellanea, MD; Flavia Briganti, MD; Paola Elda Gigliotti, MD; Carolina Goffredo, MD; Lucia Giudice, MD; Diletta Caccia, MD; Francesca Servadei, MD; Adriano De Majo, MD, PhD; et al. (Radiology Case Reports)
Mucinous carcinoma of the breast, also known as colloid carcinoma, is an uncommon type of differentiated adenocarcinoma, representing only 2% of all invasive breast carcinomas. It usually occurs in women ≥ 60 years of age. Mucinous carcinoma is characterized by clusters of epithelial tumour cells suspended in pools of extracellular mucin and is further divided in 2 subgroups, pure and mixed. Compared to invasive ductal carcinoma, mucinous carcinoma has a better prognosis, being characterized by a lower incidence of nodal involvement and a more favorable histological grade, with low proliferative activity and high expression of hormone receptors. Overall 10-year survival is estimated to be more than 90%. We present a case of a 57-year-old female patient who presented a palpable mass in the right breast for at least 2 years. On examination the whole breast appeared swollen, congestive and painless to palpation. Breast ultrasound, breast MRI and tru-cut biopsy were performed and suggested an advanced infiltrated carcinoma with mucinous aspects. Immunohistochemistry study demonstrated ER positivity (95%), PR low (5%), HER-2-Neu negativity (score 0) and proliferative index (Ki67) of 20%, determining a Luminal B-like (HER 2-negative) subtype. The patient was then candidated to mastectomy surgery and breast reconstruction with DIEP flap. Axillary lymp-nodes were sampled surgically.